1993
DOI: 10.1002/etc.5620121203
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐marsh processes: A Review

Abstract: Salt marshes are found between the high tide and the near‐shore sublittoral zones along the coasts and up estuaries of continents, primarily in the temperate zone. They flourish in regions where much silt is carried to the coastal regions by rivers or where geological processes favor erosion and suspension of silt. Salt marshes have multiple ecological and economic values. They have a high rate of primary productivity; provide habitats for many marine species (including commercially important organisms); assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 152 publications
0
53
0
3
Order By: Relevance
“…The within-subestuary factor of local-scale shoreline type (beach, wetland, bulkhead, or riprap) was also included as a fixed effect due to significant patterns identified by the local-scale analysis. Wetlands and forested land within 100 m of shore, measured at the subestuary level, were included as predictors rather than whole-watershed wetland/forested land because natural land covers (e.g., forest and wetlands) close to the shoreline can buffer against runoff of nutrients and other pollutants (Vernberg 1993) and provide critical habitat (woody debris and intertidal wetland surfaces) for aquatic mobile estuarine fauna (Everett and Ruiz 1993;Bilkovic & Roggero 2008). Models that included this full set of candidate predictors satisfied non-collinearity requirements laid out in Weller et al (2011), and correlation among all potential predictors was limited, with the absolute value of all Pearson's r < 0.65.…”
Section: System-scale Predictors Of Fish and Crustacean Abundancementioning
confidence: 99%
“…The within-subestuary factor of local-scale shoreline type (beach, wetland, bulkhead, or riprap) was also included as a fixed effect due to significant patterns identified by the local-scale analysis. Wetlands and forested land within 100 m of shore, measured at the subestuary level, were included as predictors rather than whole-watershed wetland/forested land because natural land covers (e.g., forest and wetlands) close to the shoreline can buffer against runoff of nutrients and other pollutants (Vernberg 1993) and provide critical habitat (woody debris and intertidal wetland surfaces) for aquatic mobile estuarine fauna (Everett and Ruiz 1993;Bilkovic & Roggero 2008). Models that included this full set of candidate predictors satisfied non-collinearity requirements laid out in Weller et al (2011), and correlation among all potential predictors was limited, with the absolute value of all Pearson's r < 0.65.…”
Section: System-scale Predictors Of Fish and Crustacean Abundancementioning
confidence: 99%
“…More recent studies have also shown that bacteria and microzooplankton (ciliates, heterotrophic nanoflagellates) abundances during the summer in North Inlet were at the high end of those reported in the literature [26,45]. Because the major proportion of annual planktonic primary production in North Inlet occurs during the summer [25,44], knowledge of the trophodynamics of microbial communities during this period is important to understanding overall ecosystem function in this estuary.…”
Section: Introductionmentioning
confidence: 94%
“…Odum (1988) and Vernberg (1993) noted that freshwater flow from rain events altered the existing assemblage of organisms in an estuary, and stated that more studies need to be conducted on salinity because it affects the vast majority of estuarine biota. In this study, we investigated the impact of salinity changes on estuarine fiddler crabs belonging to the species Uca minax, U. pugnax and U. pugilator in the North Inlet Estuary, South Carolina (see Fig.…”
Section: Introductionmentioning
confidence: 99%